PERTANGGUNGJAWABAN PIDANA BAGI PERS YANG MENYEBARAKAN BERITA BOHONG DI INDONESIA - Ahmad Jamaludin (VARIA HUKUM, 2022)
AbstractFreedom of the Press is a necessity in a democratic country. The Press Institute as one of the pillars of democracy has a big role in translating the values of freedom of opinion, obtaining valid information and providing access to reliable information as well as efforts to unite the nation. The era of Indonesian democracy opened the faucet for press freedom which had a positive impact, but also had a negative impact. The amount of information in the digital era that is conveyed to the public is not all information whose truth is beyond doubt, but there is also information that contains fake news, what is more worrying is that the press agencies are spreading the fake news. In the process of handling press cases, there are special regulations stipulated in the Press Law, where the handling is very different from the handling of other crimes, including the criminal accountability process which is also different from other crimes. Therefore, it is necessary for law enforcers to understand in handling press cases in Indonesia and for an understanding of who can be held responsible for criminal acts in the press which spreads fake news.AbstrakKebebasan Pers menjadi sebuah keniscayaan dalam negara demokrasi. Lembaga Pers sebagai salahsatu pilar demokrasi mempunya peranan besar dalam menterjemahkan nilai kebebasan berpendapat, mendapatkan informasi yang valid dan memberikan akses informasi yang terpercaya serta upaya untuk mempersatukan bangsa. Era demokrasi Indonesia membuka keran kebebasan pers yang punya dampak positif, namun juga punya dampak negatif. Banyaknya informasi di era digital yang disampaikan kepada masayarakat tidak semua informasi yang kebenarannya tidak diragukan lagi, namun ada juga informasi yang mengandung berita bohong, yang lebih menghawatirkan adalah yang menyebarkan berita bohong tersebut adalah Lembaga pers. Dalam proses penanganan perkara pers, terdapat regulasi yang khusus yang diatur dalam UU Pers, dimana penangananya sangat berbeda dengan penanganan kejahatan lain termasuk proses pertanggung jawaban pidaananya juga berbeda dengan tindak pidana lain. Olehkarenanya perlunya pemahaman para penegak hukum dalam menangani kasus pers di Indonesia serta perlunya pemahaman mengenai siapa yang dapat mempertanggungjawabkan perbuatan pidana pada Pers yang menyebarkan berita bohong.